2007
DOI: 10.1016/j.jvs.2007.02.046
|View full text |Cite
|
Sign up to set email alerts
|

Tissue engineering applications to vascular bypass graft development: The use of adipose-derived stem cells

Abstract: The burgeoning field of vascular tissue engineering holds promise for the creation of a practical and successful small-diameter arterial bypass graft. Many creative combinations of autologous cells and scaffolds exist along with an equally long list of microenvironmental cues used to create a functional arterial conduit. This review outlines our work using abdominal wall fat as a source of autologous stem cells for vascular tissue engineering, focusing specifically on this stem cell's availability and potency … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
67
0
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 83 publications
(69 citation statements)
references
References 19 publications
1
67
0
1
Order By: Relevance
“…Composite EC-MSC islet grafts could benefit from the immune regulatory effects of MSCs and from improved revascularization, thereby promoting transplantation at an extrahepatic site. This strategy requires a reliable source of recipient-derived ECs or endothelial precursor cells; however, human endothelial precursor cells can be obtained in relatively large numbers by sorting for circulating angiopoietin receptor Tie-2-positive cells (41) or from adipose-derived stem cells in human fat tissue (42,43). Our promising results with EC-MSC islets strongly suggest that they can contribute to the success of future clinical islet transplantation.…”
Section: Discussionmentioning
confidence: 96%
“…Composite EC-MSC islet grafts could benefit from the immune regulatory effects of MSCs and from improved revascularization, thereby promoting transplantation at an extrahepatic site. This strategy requires a reliable source of recipient-derived ECs or endothelial precursor cells; however, human endothelial precursor cells can be obtained in relatively large numbers by sorting for circulating angiopoietin receptor Tie-2-positive cells (41) or from adipose-derived stem cells in human fat tissue (42,43). Our promising results with EC-MSC islets strongly suggest that they can contribute to the success of future clinical islet transplantation.…”
Section: Discussionmentioning
confidence: 96%
“…To isolate ADSCs, subcutaneous adipose tissue of adult male Lewis rats (n= 10) was excised from their inguinal regions, cut into small pieces and cells were isolated according to the established protocols [11,19]. All of the experiments were carried out using cells that were between passages 3 and 5.…”
Section: Isolation Of Adipose-derived Stem Cells In Vitromentioning
confidence: 99%
“…Other laboratories have published data on the differentiation of ADSCs into SMCs [10][11][12][13]. In a recent study, our group established a reliable small animal model for hypocontractile bladder and demonstrated that ADSCs support the early restoration of bladder voiding with improved voiding pressures and molecular expression of contractile proteins after cell therapy [14].…”
Section: Introductionmentioning
confidence: 96%
“…94 Both Fbg and Fbn contain binding sites for various angiogenic factors, including adipose-derived stem cells and bone marrow stem cells. 178,179 Both Fbg and Fbn provide a high seeding efficacy with uniform cell distribution for certain stem cells, such as hematopoietic stem cells, endothelial progenitor cells, smooth muscle cells, and MSCs, which are potentially differentiated into vascular-promoting cells in vitro. 180 Endothelial cellāˆ’seeded-Fbn-hydrogel-induced blood vessels were shown to achieve good mechanical strength, with significant production of collagen and elastin, and showed considerable vasoreactivity within 2 weeks when implanted into 12-week-old lambs.…”
Section: Vascular Tissue Regenerationmentioning
confidence: 99%